Characterization of PBI/Graphene Oxide Composite Membranes for the SO2 Depolarized Electrolysis at High Temperature - Sergio Diaz-Abad; Sandra Fernández-Mancebo; Manuel A. Rodrigo; Justo Lobato (Membranes, 2022)
In this work, polybenzimidazole (PBI) membranes with different graphene oxide (GO) contents (0.5, 1.0, 2.0, and 3.0 wt %) as organic filler have been prepared. The X-ray diffraction confirms the incorporation of the filler into the polymeric membrane. The composite GO-based PBI membranes show better proton conductivity at high temperature (110–170 °C) than the pristine one. Moreover, the hydrophobicity of the PBI membranes is also improved, enhancing water management. The chemical stability demonstrates the benefit of the incorporation of GO in the PBI matrix. What is more, the composite PBI-based membranes show better phosphoric acid retention capability. For the first time, the results of the SO2-depolarized electrolysis for hydrogen production at high temperature (130 °C) using phosphoric acid-doped polybenzimidazole (PBI) membranes with the different GO contents are shown. The benefit of the organic filler is demonstrated, as H2SO4 production is 1.5 times higher when the membrane with a content of 1 wt % of GO is used. Moreover, three times more hydrogen is produced with the membrane containing 2 wt % of GO compared with the non-modified membrane. The obtained results are very promising and provide open research for this kind of composite membranes for green hydrogen production by the Westinghouse cycle.